Moderate Resolution Imaging Spectroradiometer (MODIS) and Aerosol Robotic Network (AERONET) retrievals during dust outbreaks over the Mediterranean - SANTESE, MONICA; DE TOMASI, Ferdinando; PERRONE, Maria Rita (2007)
Moderate Resolution Imaging Spectroradiometer (MODIS)–ocean aerosol products and corresponding Aerosol Robotic Network (AERONET) data retrieved during Sahara dust outbreaks that occurred over the central Mediterranean basin have been analyzed, to contribute to the validation of MODIS retrievals during dust-loading conditions. It is shown that MODIS aerosol optical depths (AODM) retrieved at 550 nm for window sizes of 50 × 50 km2 centered at different Mediterranean AERONET sites are in satisfactory accordance to corresponding AERONET optical depths (AODA) colocated in space and time: Correlation factor and slope of the linear regression are 0.86 and 1.04, respectively, and 42% of data points are within the prespecified accuracy range. However, the plot of the differences (AODM – AOD A ) versus AOD A has revealed that the differences (AODM – AOD A ) are almost positive and increase with AOD A , and has led assuming that MODIS overestimates AODs mainly during high dust load conditions. The comparison of MODIS-ocean and corresponding AERONET fine-mode fractions (η M and η A, respectively) colocated in space has revealed that the MODIS-ocean inversion algorithm overestimates the contribution of fine-mode particles for dust-dominated aerosols: (η M − η A) difference values vary within the 0.11–0.24 range. In addition, the comparison of MODIS-ocean and corresponding AERONET volume size distributions has revealed that the latter results are mainly due to the poor sensitivity of the MODIS-ocean inversion algorithm to the concentration of coarse-mode particles during dust outbreaks. The frequency distributions of MODIS fine and coarse volume modal radii are found to be rather close to corresponding AERONET frequency distributions. Received 31 January 2007; accepted 30 May 2007;